Antimicrobial macromolecules : synthesis methods and future applications - Li, Xiang (2013)
This review article presents important and recent progress in the manufacture and application of antimicrobial macromolecules. Microbial infections continue to endanger human health and pose a great economic burden to society. To resolve this crisis, huge efforts to improve or develop macromolecules that can inhibit pathogens without incurring pathogen resistance are required and actively ongoing. Synthetic antimicrobial macromolecules which include antimicrobial peptides (AMPs), polymers and peptide–polymer hybrids represent a huge class of molecules which can incur effective antimicrobial therapy due to their unique biochemical properties. The use of these antimicrobial macromolecules which target the cytoplasmic membrane of microbes, is a promising approach to lower the propensity of pathogen resistance development. Therefore, huge efforts to synthesize these molecules at scales and purities that enable their structure-function and clinical studies are actively underway. Due to the high cost involved in extracting AMPs from natural sources, biological processes are being developed to economically manufacture AMPs at large scale. Synthetic AMP analogs are also being engineered to further improve antimicrobial potency and lower synthesis cost. Synthetic polymers have also been found to exhibit excellent antimicrobial properties which are comparable to those of natural AMPs. Various antimicrobial polymers have been synthesized based on the amphiphilicity of natural AMPs. Although the facile synthesis of polymers poses no cost problems, numerous synthetic antimicrobial polymers are disadvantaged by high toxicity to mammalian cells due to their non-selectivity. To combine the advantages of AMPs and antimicrobial polymers, peptide-polymer hybrid macromolecules are actively being developed, with a few effective and strongly microbicidal models recently demonstrated. With the advancement of biochemical engineering tools and chemical synthesis methods, these antimicrobial macromolecules can be specifically designed to be highly selective, broad spectrum and biocompatible. In this review, we summarize the recent advances and challenges in the manufacture of these antimicrobial macromolecules. Based on their antimicrobial mechanisms, their applications in addressing challenges associated with infectious disease and antibiotic-resistance are also discussed.